An andragogy perspective in thoriqoh qodiriyah wanaqsyabandiyyah activity as nn effort of spiritual development - Asmono, Riska Indriani; Riyanto, Yatim; Mardliyah, Sjafiatul; Rofiah, Khofidotur (Universitas Negeri Semarang, 2023)
The more diverse types of communities in society show the high interest in adult learning in awareness of lifelong education. A religious community named Thoriqoh Qodiriyah wa Naqsyabandiyyah as a unifying medium for the interests and goals of studying religion and a medium for self-development. The thoriqoh activity was held at the Jami' Imaduddin Pondok Pesantren Tarbiaytul Ulum, Sumursongo, Magetan which was attended by congregations from various groups of people with diverse educational, economic, social and cultural backgrounds. This study aims to analyze the andragogical perspective on thoriqoh qodiriyah wa naqsyabandiyyah activities as an effort to foster spirituality. This type of research is qualitative with a phenomenological approach that focuses on exploring the personal experiences of the congregation with one another. The sampling technique uses purposive sampling and data validity techniques use source triangulation. The results of this study indicate that thoriqoh activities fulfill the principles of adult education, in which there are characteristics of adult learning inherent in them. People who are members of this activity voluntarily and with determination to practice the teachings as a result of spiritual development.